The Physical Mechanism of Radio-quiet Turn-on Changing-look Active Galactic Nuclei - Li, Shuang-Liang; Cao, Xinwu (The Astrophysical journal, 2025)
It is suggested that the variation of the mass accretion rate in the accretion disk may be responsible for the occurrence of most changing-look active galactic nuclei (CL AGNs). However, the viscous timescale of a thin disk is far longer than the observed timescale of CL AGNs. Though this problem can be resolved by introducing the large-scale magnetic field, the mechanism for radio-quiet CL AGNs with a weak/absent large-scale magnetic field remains a mystery. In this work, we assume that the thin accretion disk is collapsed from the inner advection-dominated accretion flow (ADAF) instead of being formed from the outer thin disk through advection. This idea is tested by comparing the cooling timescale ( t cool ) of an ADAF with the observed timescale ( t tran ) of turn-on CL AGNs. We compile a sample of 102 turn-on CL AGNs from the archived data and calculate the cooling timescale of an ADAF with the critical mass accretion rate based on some conventional assumptions. It is found that t cool is much shorter than t tran in most of the CL AGNs, which validates our assumption, though t cool is not consistent with t tran ( t cool  <  t tran ). However, this is reasonable since most of the CL AGNs were observed only two times, indicating that the observed timescale t tran is the maximum value because the changing-look behavior can indeed happen before the second observation.